Etika Alquran Menuju Masyarakat Adil Dan Makmur - Muhammad Chirzin (AL QUDS : Jurnal Studi Alquran dan Hadis, 2017)
A fair, prosperous and happy life are the inner desire of every human being. In order to realize these ideals, human beings necessarily recognize each other's potential, advantages and / or disadvantages to complement each other; mutual learning, mutual giving and receiving.The presence of the prophets brought the Shari'ah of Allah SWT with the aim of establishing a just humanitarian system. The just society is reflected in the right and proper group life.In the context of human relationships, justice in the Quran contains three meanings. First, fair in the same sense. Second, fair in a balanced sense. Third, fair in the sense of attention to the rights of individuals and give those rights to each owner and get a social justice.A prosperous society is a prosperous, capable, and rich society.In the context of the state, prosperity is a state of affluence that encompasses the lives of all people.Islamic justice is superior to any formal justice of any human law. It penetrates deep down to the deepest feelings. One of the prerequisites to realize the harmony of human life is peace. When there is a dispute, it is necessarily settled in the most fair manner. For that every member of the community must be willing to sacrifice for the common good and strive for the common goal. Society will undoubtedly help each other to realize a just and prosperous life all of time.